2013
DOI: 10.1002/oti.1345
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring the Usability of Nintendo Wii Fit among Persons with Multiple Sclerosis

Abstract: The purpose of this study was to examine the usability of Nintendo Wii Fit to promote physical activity in adults with multiple sclerosis. Qualitative interviews were conducted as part of a pilot study that examined the health outcomes of a 14-week Wii Fit home-exercise programme in 30 adults with multiple sclerosis. We found participants reported that Wii Fit helped build confidence in abilities, achieve goals related to engagement in leisure activities and remove barriers associated with going to a gym to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 27 publications
5
57
0
3
Order By: Relevance
“…There are a mix of study designs (Table 1) ranging from case study to RCT; [24][25][26][27][28] there is no consensus about the (a) outcome measures, (b) the duration/frequency of training sessions (training sessions have lasted from 1 day up to a proposed 12 months), 29,30 and (c) the types of game played on these platformsall familiar issues in exergaming research. The one common factor between all the studies reported here is the use of commercially available games, [24][25][26][27][28][29][30][31][32][33][34][35] i.e. not games which are specific to the needs of PwMS.…”
Section: The Current State Of Exergaming Research In Pwmsmentioning
confidence: 99%
“…There are a mix of study designs (Table 1) ranging from case study to RCT; [24][25][26][27][28] there is no consensus about the (a) outcome measures, (b) the duration/frequency of training sessions (training sessions have lasted from 1 day up to a proposed 12 months), 29,30 and (c) the types of game played on these platformsall familiar issues in exergaming research. The one common factor between all the studies reported here is the use of commercially available games, [24][25][26][27][28][29][30][31][32][33][34][35] i.e. not games which are specific to the needs of PwMS.…”
Section: The Current State Of Exergaming Research In Pwmsmentioning
confidence: 99%
“…Os autores sinalizaram que as barreiras deveriam ser identificadas com o objetivo de ampliar o uso eficaz do recurso pelo paciente (PLOW;FINLAYSON, 2013).…”
Section: Discussionunclassified
“…Some patients were intimidated by the Nintendo Wii Fit owing to concerns about falling, and some disliked exergaming feedback because it reminded them of their impairments [103]. Furthermore, some were unsure how to use a video game [68], so appropriate training is needed.…”
Section: Discussionmentioning
confidence: 99%